2022
DOI: 10.21037/apm-22-104
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma levels of osteoglycin in cardiovascular patients: a systematic review and meta-analysis

Abstract: Background: To evaluate the levels of osteoglycin (OGN) in patients with cardiovascular disease.Methods: A meta-analysis was conducted on retrospective studies that compared patients with and without cardiovascular disease. Data including the levels of OGN, low density lipoprotein (LDL), and high density lipoprotein (HDL) were analyzed and expressed as mean differences (MD) with a 95% confidence interval (CI).Results: This meta-analysis included 6 studies with a total of 1,443 patients. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Evidence for the involvement of OGN in the fibrosis of cardiovascular disease is abundant. A meta-analysis revealed that the blood concentration of OGN in patients with cardiovascular disease is significantly elevated compared to that in control patients, indicating that OGN may play an important role in cardiovascular disease [ 62 ]. OGN is expressed by cardiac fibroblasts, vascular smooth muscle cells, and cardiomyocytes [ 63 , 64 ].…”
Section: Ogn As a Regulator Of Fibrosismentioning
confidence: 99%
“…Evidence for the involvement of OGN in the fibrosis of cardiovascular disease is abundant. A meta-analysis revealed that the blood concentration of OGN in patients with cardiovascular disease is significantly elevated compared to that in control patients, indicating that OGN may play an important role in cardiovascular disease [ 62 ]. OGN is expressed by cardiac fibroblasts, vascular smooth muscle cells, and cardiomyocytes [ 63 , 64 ].…”
Section: Ogn As a Regulator Of Fibrosismentioning
confidence: 99%